2004
DOI: 10.1117/12.535347
|View full text |Cite
|
Sign up to set email alerts
|

Angiographic analysis of blood flow modification in cerebral aneurysm models with a new asymmetric stent

Abstract: We have built new asymmetric stents for minimally invasive endovascular treatment of cerebral aneurysms. Each asymmetric stent consists of a commercial stent with a micro-welded circular mesh patch. The blood flow modification in aneurysm-vessel phantoms due to these stents was evaluated using x-ray angiographic analysis. However, the density difference between the radiographic contrast and the blood gives rise to a gravity effect, which was evaluated using an initial optical dye-dilution experiment. For the r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
13
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 16 publications
1
13
0
Order By: Relevance
“…We reported two orders of magnitude decrease in the velocity and vorticity, and reduced aneurysmal wall shear stress. Additionally, in-vitro angiographic studies using the AVS14, 18 demonstrated drastic reduction of iodine contrast in the aneurysm dome and prolonged contrast presence following injection, signifying decreased flow within the aneurysm.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…We reported two orders of magnitude decrease in the velocity and vorticity, and reduced aneurysmal wall shear stress. Additionally, in-vitro angiographic studies using the AVS14, 18 demonstrated drastic reduction of iodine contrast in the aneurysm dome and prolonged contrast presence following injection, signifying decreased flow within the aneurysm.…”
Section: Introductionmentioning
confidence: 99%
“…Intracranial aneurysm (IA) treatment using flow alteration induced by stents is a subject studied intensely by a number of endovascular research groups 1-18. The primary hypothesis is that flow diversion can induce intra-aneurysmal thrombus formation thereby resulting in aneurysm exclusion from the circulation 19.…”
Section: Introductionmentioning
confidence: 99%
“…Certain studies have suggested that, especially in intracranial aneurysms, the transport of contrast does not follow the transport of blood. Due to its higher density, contrast is said to settle out of the blood in the gravity direction within aneurysm sacs [22, 23]. This notion has not been borne out by experiments conducted to investigate the mixing of angiographic contrast with blood under conditions similar to most cerebral angiographic acquisitions [24].…”
Section: Discussionmentioning
confidence: 99%
“…This stent has a significant advantage over the Neuroform stent in that it is 80% resheathable into the delivery microcatheter. Asymmetric stents in which a portion of the stent is covered with a low-porosity, stainless steel patch may be useful in regions with high perforator densities (62,70,81,82,122,153). Telescoping stents or unique stent strut designs may also prove to be useful techniques for flow diversion without the need for coiling (74).…”
Section: Cerebral Aneurysmsmentioning
confidence: 99%